Pengaruh Pengelolaan Alokasi Dana Desa Terhadap Kesejahteraan Masyarakat: Studi Kasus Pada Kampung Sumber Boga Distrik Masni Kabupaten Manokwari - Mus Mualim; Marcus R. Maspaitella (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2021)
The concept of development in Indonesia is an effort to increase equitable distribution of development and its results through sectoral policies and community performance, especially in rural areas. To prosper the village community, the government issued a special budget for villages through the Village Fund Allocation (VFA) to increase community independence, including the Sumber Boga Village. The amount of VFA for Sumber Boga Village naturally should be followed by an increase in the welfare of the community. This study aims to analyze the effect of the management of VFA on the welfare of the community in Sumber Boga Village, Masni District, Manokwari Regency. The type of research used is qualitative and descriptive research using 88 heads of families as respondents obtained using purposive sampling technique. Regression analysis was carried out and the results show that either partially or simultaneously, all independent variables affect people's welfare.